Pentaerythritol p-hydroxybenzoate ester-based zinc metal alkoxides as multifunctional antimicrobial thermal stabilizer for PVC. (November 2020) - Zhang, Manqi; Han, Wenyuan; Hu, Ximin; Li, Degang; Ma, Xinjun; Liu, Hongliang; Liu, Lihong; Lu, Weidong; Liu, Shaomin
Highlights: Pentaerythritol p-hydroxybenzoate ester-zinc metal alkoxides (PHE-Zn) was synthesized as multifunctional PVC additive. Addition of PHE-Zn significantly improved initial white color and long-term thermal stability of PVC. PHE-Zn had excellent inherent biocidal effect against S. aureus and e coli. PHE-Zn enhanced plasticization and promoted ductility of the resultant PVC. Abstract: There is a wide demand for PVC products with microbiocidal property. For this purpose, additional antimicrobial agents have to be added. In this work, we synthesized pentaerythritol p-hydroxybenzoate ester-based zinc metal alkoxides (PHE-Zn) additive as highly efficient antibacterial agent, thermal stabilizer, plasticizer and lubricant for PVC. PHE-Zn was characterized by Fourier-transform infrared spectrometer (FT-IR), X-ray photoelectron spectroscopy (XPS), and elemental analysis. The results confirm the formation of R-O-Zn bonds and the molecular structure of PHE-Zn. The property enhancement of PVC by PHE-Zn were investigated by conductivity, oven aging, and torque rheological tests. PHE-Zn not only contributes to excellent initial whiteness and significant long-term thermal stability (without color change up to 90 min), but also improves plasticization and lubrication of PVC. In addition, using E. coli ( E. coli ) and Staphylococcus aureus ( S. aureus ) as typical microorganisms, the antibacterial properties of PHE-Zn stabilized PVC were tested. PVC with 4 phr PHE-Zn displayed high killing rates against E. coli and S. aureus (97.92% and 91.84%, respectively). Further experiments showed that PHE-Zn was a contact-active antibacterial agent. Moreover, the mechanisms for the enhanced thermal stability and biocidal property of PHE-Zn on PVC was explored.